2011
DOI: 10.1371/journal.pcbi.1002088
|View full text |Cite
|
Sign up to set email alerts
|

The Eps8/IRSp53/VASP Network Differentially Controls Actin Capping and Bundling in Filopodia Formation

Abstract: There is a body of literature that describes the geometry and the physics of filopodia using either stochastic models or partial differential equations and elasticity and coarse-grained theory. Comparatively, there is a paucity of models focusing on the regulation of the network of proteins that control the formation of different actin structures. Using a combination of in-vivo and in-vitro experiments together with a system of ordinary differential equations, we focused on a small number of well-characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 48 publications
(108 reference statements)
7
87
0
Order By: Relevance
“…An IRSp53-interacting protein is Eps8 (epidermal growth factor receptor kinase substrate 8). Eps8 can cap barbed ends of actin filaments when binding to Abi-1, whereas the association of Eps8 with IRSp53 induces filopodium formation by cross-linking actin filaments (30,35,36). These findings suggest that Eps8 can induce or inhibit the filopodium formation depending on its binding proteins.…”
Section: Discussionmentioning
confidence: 95%
“…An IRSp53-interacting protein is Eps8 (epidermal growth factor receptor kinase substrate 8). Eps8 can cap barbed ends of actin filaments when binding to Abi-1, whereas the association of Eps8 with IRSp53 induces filopodium formation by cross-linking actin filaments (30,35,36). These findings suggest that Eps8 can induce or inhibit the filopodium formation depending on its binding proteins.…”
Section: Discussionmentioning
confidence: 95%
“…As in the agent-based model [5,32] filopodia extension and retraction are dependent on [VEGF] and they are modeled in a non-spatial manner by directly capturing the positive feedback between the VEGF ligand (V) and filopodia (filo) mediated VEGF sensing: where n represents the cooperativity in F-actin polymerization and filopodia formation (i.e. a cooperative action in n molecules of F-actin filaments leading to filopodia formation) [33]. Previous studies have shown cooperativity between at least two pathways downstream of VEGFR2 activation leading to F-actin polymerization [34].…”
Section: Methodsmentioning
confidence: 99%
“…3D). Owing to its localization in filopodia tips and the possible involvement of the I-BAR protein IRSp53 in filopodia formation (Millard et al, 2005;Vaggi et al, 2011), we quantified the total number of filopodia in randomly migrating IBARa-null and WT cells using phase-contrast microscopy. However, and consistent with a recent report (Veltman et al, 2011), we could not find a significant difference; both cell lines formed about six filopodia on average (Fig.…”
Section: Generation and Analysis Of Ibara-null Mutantsmentioning
confidence: 99%
“…Previous studies have suggested that I-BAR proteins regulate the formation of actin protrusions through interactions with membranes, actin and other cytoskeletal regulators, for instance as described for IRSp53 with VASP (Vaggi et al, 2011), or the Diaphanous-related formin mDia1 and the Scar/ WAVE-complex subunit WAVE2 (Goh et al, 2011). In addition, pathogens such as enterohaemorrhagic Escherichia coli (EHEC) use these interactions to recruit the actin-assembly machinery for the formation of actin pedestals (de Groot et al, 2011).…”
Section: Introductionmentioning
confidence: 99%